Co-prescription of opioids with benzodiazepine and other co-medications among opioid users: differential in opioid doses - Zin, Che Suraya; Ismail, Fadhilah (Dove Medical Press Ltd., 2017)
Purpose: This study investigated the patterns of opioid co-prescription with benzodiazepine and other concomitant medications among opioid users. Opioid dose in each type of co-prescription was also examined. Patients and methods: This cross-sectional study was conducted among opioid users receiving concomitant medications at an outpatient tertiary hospital setting in Malaysia. Opioid prescriptions (morphine, fentanyl, oxycodone, dihydrocodeine and tramadol) that were co-prescribed with other medications (opioid + benzodiazepines, opioid + antidepressants, opioid + anticonvulsants, opioid + antipsychotics and opioid + hypnotics) dispensed from January 2013 to December 2014 were identified. The number of patients, number of co-prescriptions and the individual mean opioid daily dose in each type of co-prescription were calculated. Results: A total of 276 patients receiving 1059 co-prescription opioids with benzodiazepine and other co-medications were identified during the study period. Of these, 12.3% of patients received co-prescriptions of opioid + benzodiazepine, 19.3% received opioid + anticonvulsant, 6.3% received opioid + antidepressant and 10.9% received other co-prescriptions, including antipsychotics and hypnotics. The individual mean opioid dose was <100 mg/d of morphine equivalents in all types of co-prescriptions, and the dose ranged from 31 to 66 mg/d in the coprescriptions of opioid + benzodiazepine. Conclusion: Among the opioid users receiving concomitant medications, the co-prescriptions of opioid with benzodiazepine were prescribed to 12.3% of patients, and the individual opioid dose in this co-prescription was moderate. Other co-medications were also commonly used, and their opioid doses were within the recommended dose. Future studies are warranted to evaluate the adverse effect and clinical outcomes of the co-medications particularly in long-term opioid users with chronic non-cancer pain.